2013
DOI: 10.1371/journal.pone.0080161
|View full text |Cite
|
Sign up to set email alerts
|

Darwin’s Duchenne: Eye Constriction during Infant Joy and Distress

Abstract: Darwin proposed that smiles with eye constriction (Duchenne smiles) index strong positive emotion in infants, while cry-faces with eye constriction index strong negative emotion. Research has supported Darwin’s proposal with respect to smiling, but there has been little parallel research on cry-faces (open-mouth expressions with lateral lip stretching). To investigate the possibility that eye constriction indexes the affective intensity of positive and negative emotions, we first conducted the Face-to-Face/Sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 39 publications
5
23
0
Order By: Relevance
“…Because action units are exhaustive and mutually exclusive, nearly all possible facial expressions can be precisely and unambiguously identified in relation to combinations and sequences of its constituent actions. Baby FACS validity has been demonstrated by its cross-cultural invariance and ability to distinguish responses to different emotion elicitors (Rosenstein and Oster;Camras et al, 2003;Oster, 2003, 2005, Bolzani Dinehart et al, 2005Mattson et al, 2013). Importantly, Oster et al have shown that the facial expressions of infants with craniofacial anomalies can be reliably coded with Baby FACS (Oster, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Because action units are exhaustive and mutually exclusive, nearly all possible facial expressions can be precisely and unambiguously identified in relation to combinations and sequences of its constituent actions. Baby FACS validity has been demonstrated by its cross-cultural invariance and ability to distinguish responses to different emotion elicitors (Rosenstein and Oster;Camras et al, 2003;Oster, 2003, 2005, Bolzani Dinehart et al, 2005Mattson et al, 2013). Importantly, Oster et al have shown that the facial expressions of infants with craniofacial anomalies can be reliably coded with Baby FACS (Oster, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…As noted above, the Still-Face paradigm is one of the most well-validated procedures for inducing positive and negative affect in mothers and infants [39], [38]. During the Play episode, mother and infant positive affect and joint attention are frequent; during the Still Face episode infant positive affect and attention to the mother decrease and infant negative affect increases relative to Play.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that eye constriction (AU6; the Duchenne marker) and mouth opening (AU27) each index the intensity of both positive and negative infant facial expressions (Fogel et al, 2000; Fox & Davidson, 1988; Mattson et al, 2013; Messinger, 2002; Messinger et al, 2008; Messinger & Fogel, 2007; Messinger et al, 2001; Messinger et al, 2012). In adults, eye constriction (AU6) and mouth opening (AU27) are characteristic—although not requisite—in facial expressions of joyful positive affect (Ambadar et al, 2009), affectively negative pain expressions (Williams, 2002), and other extreme expressions such as those associated with orgasm (Fernández-Dols et al, 2011).…”
mentioning
confidence: 99%